Controls on Water-Column Respiration Rates in a Coastal Plain Estuary: Insights from Long-Term Time-Series Measurements - David Prichett; Joan M. Bonilla Pagan; Casey L. S. Hodgkins; Jeremy M. Testa (Estuaries and Coasts, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

P06-20 OMICs approaches linking effects of endocrine disrupters on developing rat hippocampus with impaired memory function in adult offspring and human stem cell-derived in vitro models - W. Lichtensteiger; C. Bassetti-Gaille; H. Rehrauer; N. Caporale; B. Linillos Pradillo; L. Rancan; H. Idrissi; L. Miguélez-Salas; J. Felix; S.D. Paredes; S. Evangelista; M. de la Fuente; et al. (Toxicology Letters, 2024)

OS04-03 Unravelling the impact of endocrine disruptors on human neurodevelopment through the lens of brain organoids - M. Lessi; N. Caporale; M.T. Rigoli; C. Cheroni; S. Stucchi; G. Matassa; D. Bulgheresi; A. Valenti; G. Testa (Toxicology Letters, 2024)

Life Cycle Assessment of a system for the extraction and transformation of Waste Water Treatment Sludge (WWTS)-derived lipids into biodiesel - B. Notarnicola; G. Tassielli; P.A. Renzulli; R. Di Capua; F. Astuto; S. Riela; A. Nacci; M. Casiello; M.L. Testa; L.F. Liotta; C. Pastore (Science of The Total Environment, 2023)

Large-Scale Spatial and Temporal Patterns and Importance of Sediment–Water Oxygen and Nutrient Fluxes in the Chesapeake Bay Region - W. R. Boynton; M. A. C. Ceballos; C. L. S. Hodgkins; D. Liang; J. M. Testa (Estuaries and Coasts, 2023)

Long-term Annual Aerial Surveys of Submersed Aquatic Vegetation (SAV) Support Science, Management, and Restoration - Robert J. Orth; William C. Dennison; Cassie Gurbisz; Michael Hannam; Jeni Keisman; J. Brooke Landry; Jonathan S. Lefcheck; Kenneth A. Moore; Rebecca R. Murphy; Christopher J. Patrick; Jeremy Testa; Donald E. Weller; et al. (Estuaries and Coasts, 2022)
Aerial surveys of coastal habitats can uniquely inform the science and management of shallow, coastal zones, and when repeated annually, they reveal changes that are otherwise difficult to assess from ground-based surveys. This paper reviews the utility of a long-term (1984–present) annual aerial monitoring program for submersed aquatic vegetation (SAV) in Chesapeake Bay, its tidal tributaries, and nearby Atlantic coastal bays, USA. We present a series of applications that highlight the program’s importance in assessing anthropogenic impacts, gauging water quality status and trends, establishing and evaluating restoration goals, and understanding the impact of commercial fishing practices on benthic habitats. These examples demonstrate how periodically quantifying coverage of this important foundational habitat answers basic research questions locally, as well as globally, and provides essential information to resource managers. New technologies are enabling more frequent and accurate aerial surveys at greater spatial resolution and lower cost. These advances will support efforts to extend the applications described here to similar issues in other areas.

Biogeochemical states, rates, and exchanges exhibit linear responses to large nutrient load reductions in a shallow, eutrophic urban estuary - Jeremy M. Testa; Walter R. Boynton; Casey L. S. Hodgkins; Amanda L. Moore; Eva M. Bailey; Johanna Rambo (Limnology and Oceanography, 2022)
We examined responses of water‐column conditions, sediment‐water fluxes, ecosystem metabolism, and nutrient export in the Back River estuary during the past three decades following multiple phases of nutrient load reductions from a large wastewater treatment plant. Total nitrogen (TN) loads from the treatment plant declined from 7000 kg N d −1 in the mid‐1980s to 1500 kg N d −1 following the implementation of enhanced nutrient removal in late 2017. Total phosphorus (TP) loads declined by ~90% from peaks in the mid‐1980s–1990s and have been stable ever since. In response, TN and TP concentrations measured since 1985 show declines that generally mirror that of loads from the treatment plant, and box model computations suggest significant reductions in nutrient export to adjacent Chesapeake Bay. As a consequence, water‐column chlorophyll a (Chl a ) concentrations have declined modestly over the record, despite inter‐annual variability. This reduction in Chl a coincided with a reduced frequency of nitrogen and phosphorus concentrations that would saturate phytoplankton growth, as well as reductions in ecosystem gross primary production and respiration derived from high‐frequency oxygen time‐series. Sediment‐water fluxes of dissolved nitrogen, phosphorus, and oxygen, as well as associated sediment concentrations of nitrogen, phosphorus, and carbon also declined over the record. These temporal patterns were reproduced in a 35‐yr model simulation that suggests a relatively rapid response to reduced organic matter deposition changes. Finally, the recycling of ammonium for a given TN load declined substantially, consistent with high observed rates of denitrification, indicating that well‐mixed estuaries can recover relatively rapidly in response to nutrient remediation.

Oxygen and Nutrient Exchanges at the Sediment-Water Interface: a Global Synthesis and Critique of Estuarine and Coastal Data - W. R. Boynton; M. A. C. Ceballos; E. M. Bailey; C. L. S. Hodgkins; J. L. Humphrey; J. M. Testa (Estuaries and Coasts, 2018)

Progress and Challenges in Coupled Hydrodynamic-Ecological Estuarine Modeling - Neil K. Ganju; Mark J. Brush; Brenda Rashleigh; Alfredo L. Aretxabaleta; Pilar del Barrio; Jason S. Grear; Lora A. Harris; Samuel J. Lake; Grant McCardell; James O’Donnell; David K. Ralston; Richard P. Signell; et al. (Estuaries and Coasts, 2016)

GC–MS characterisation and biological activity of essential oils from different vegetative organs of Plectranthus barbatus and Plectranthus caninus cultivated in north Italy - F. Gelmini; P. Squillace; C. Testa; A.C. Sparacino; S. Angioletti; G. Beretta (Natural Product Research, 2015)

Diazinon and Permethrin Mitigation Across a Grass–Wetland Buffer - M. T. Moore; R. Kröger; M. A. Locke; R. E. Lizotte; S. Testa; C. M. Cooper (Bulletin of Environmental Contamination and Toxicology, 2014)

Understanding biological dynamics: following cells and molecules to track functions and mechanisms - A. Palamidessi; I. Testa; E. Frittoli; S. Barozzi; M. Garrè; D. Mazza; P. P. Di Fiore; A. Diaspro; G. Scita; Mario Faretta (European Biophysics Journal, 2010)

CT assessment in canine meningoencephalomyelitis - V. Drago; G. Fatone; A. Testa; S. Reale; O. Paciello; L. Meomartino (Veterinary Research Communications, 2008)

Photoactivation of pa-GFP in 3D: optical tools for spatial confinement - I. Testa; M. Garrè; D. Parazzoli; S. Barozzi; I. Ponzanelli; D. Mazza; M. Faretta; A. Diaspro (European Biophysics Journal, 2008)

The influence of stream habitat and water quality on macroinvertebrate communities in degraded streams of northwest Mississippi - J.D. Maul; J.L. Farris; C.D. Milam; C.M. Cooper; S. Testa; D.L. Feldman (Hydrobiologia, 2004)

The diet of Weddell seals in McMurdo Sound, Antarctica as determined from scat collections and stable isotope analysis - J. M. Burns; S. J. Trumble; M. A. Castellini; J. W. Testa (Polar Biology, 1998)